AGGRESSIVE SOLID PSEUDOPAPILLARY NEOPLASM OF THE PANCREAS WITH MULTIORGAN INFILTRATION AND SYNCHRONOUS HEPATIC AND INTESTINAL METASTASES: A CASE REPORT - Gunawan, Vidro Alif; Fahriza Utama; Rudyanto; Gunawan Tohir; Khairani, Lilis; Ghiffari, Ahmad (Cendekia Medika: Jurnal Stikes Al-Ma`arif Baturaja, 2026)
Solid pseudopapillary neoplasm (SPN) of the pancreas is a rare epithelial tumor that predominantly affects young women and is generally regarded as a low-grade malignant neoplasm with favorable prognosis after complete surgical resection. However, a small subset of cases may exhibit aggressive behavior, including local infiltration and distant metastases. This case is noteworthy because it demonstrates that SPN may present with indolent and nonspecific symptoms despite already showing aggressive intraoperative findings. A 25-year-old woman presented with a 3-month history of intermittent dull epigastric pain, progressive abdominal enlargement, early satiety, abdominal discomfort, and occasional nausea. Physical examination revealed abdominal distension with a palpable mass in the epigastric to left hypochondriac region. Abdominal ultrasonography demonstrated a pancreatic mass measuring approximately 6–8 cm with solid and cystic components, while computed tomography showed a well-defined encapsulated solid-cystic pancreatic mass suggestive of SPN. The patient underwent tumor resection. Intraoperatively, infiltration to the bowel, ovary, and pancreas, as well as hepatic and intestinal synchronous metastaseses, were identified, without major vascular involvement. Histopathologic examination revealed pseudopapillary structures composed of monomorphic tumor cells with cystic degeneration and hemorrhage, consistent with SPN. SPN should be considered in young women presenting with slowly progressive, nonspecific abdominal symptoms and a large solid-cystic pancreatic mass. The main contribution of this case is to emphasize that SPN, although usually indolent, may already demonstrate aggressive behavior at presentation. Integration of clinical presentation, imaging, intraoperative findings, and histopathology remains essential for diagnosis and surgical decision-making, particularly in resource-limited settings where tumor markers and immunohistochemistry are not available.